2014
DOI: 10.1016/j.tsf.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Improving corrosion resistance of AZ31B magnesium alloy via a conversion coating produced by a protic ammonium-phosphate ionic liquid

Abstract: Magnesium alloys are susceptible to corrosion because of their high reactivity and low electrode potential. The present work introduces a conversion coating using a protic ammonium-phosphate ionic liquid (IL). Initial results on the Mg AZ31B alloy have demonstrated substantially improved corrosion resistance for the IL treatment at 300 °C (IL_300C) compared to the treatment at room temperature. Potentiodynamic polarization analysis of the IL_300C treated Mg surface in a NaCl solution exhibited a strong passiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…From the SEM images, it can be seen that with the growth of the alkyl chain, more and more pittings are formed on the surface of the copper sheets. It can be concluded that for [Ch][MA] ILs, the longer the alkyl chain is, the more severe the corrosion . But the corrosion of all the [Ch][MA] ILs are much lower than that of L‐B104.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the SEM images, it can be seen that with the growth of the alkyl chain, more and more pittings are formed on the surface of the copper sheets. It can be concluded that for [Ch][MA] ILs, the longer the alkyl chain is, the more severe the corrosion . But the corrosion of all the [Ch][MA] ILs are much lower than that of L‐B104.…”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that for [Ch] [MA] ILs, the longer the alkyl chain is, the more severe the corrosion. 31 But the corrosion of all the [Ch][MA] ILs are much lower than that of L-B104. On the basis of the above analysis, it can be concluded that the corrosion resistance of [Ch][MA] ILs is superior to that of L-B104.…”
Section: Characterizationmentioning
confidence: 99%
“…It is well known that magnesium alloys have been widely applied in automobile, aerospace, electronic communication and recreational industries due to their low density, high strength and excellent machinability . However, corrosion problems are often encountered for magnesium alloys when exposed in seawater, humid atmosphere with organic/inorganic acids and other salts because of their high chemical reactivity .…”
Section: Introductionmentioning
confidence: 99%
“…They are generally nonvolatile, high thermal stability, wide and stable electrochemical window [15], nonflammable and can have a low toxicity, thus show promise as replacements for toxic molecular solvents [16]. Few works involved ILs treatment for corrosion protection of magnesium metal based on phosphates, for example trihexyl (tetradecyl) phosphonium bis (trifluoromethylsulfonyl) amide ([P 6,6,6,14 ] [17], ammonium phosphate IL [18] and halogen-free phosphonate ILs [19].…”
Section: Introductionmentioning
confidence: 99%